Longitudinal relationship between social media and e-cigarette use among adolescents: the roles of internalizing problems and academic performance - Luxi Zhang; Song Harris Ao; Xinshu Zhao (BMC, 2023)
Abstract Background Prior research has investigated the influence of social media on e-cigarette use among adolescents, predominantly through the display of e-cigarette content and advertisements. However, the psychological mechanism underlying this relationship remains underexplored. This study aims to address the mediating effect of youths internalizing problems and elucidate the moderating effect of academic performance from a longitudinal perspective. Methods Panel data from the Public Assessment of Tobacco and Health (PATH) Study Waves 3-5 (2015-2019) were utilized in this study. The sample consisted of 3,975 youths between the ages of 12 and 17 years old. A moderated mediation model was utilized for analyses. Results Adolescents using social media more frequently in Wave 3 reported higher odds of internalizing problems in Wave 4 (bp = 0.061, p < .01), which led to more e-cigarette use in Wave 5 (bp = 0.029, p < .01). A negative moderating effect of academic performance was found in the association between internalizing problems and e-cigarette use (bp=-0.088, p < .05). Conclusions Frequent social media use among young individuals leads to an increase in e-cigarette use through enhanced internalizing problems. However, adolescents who perform well academically exhibit higher resistance to e-cigarette use. Based on our findings, we recommend that tailored anti-e-cigarette campaigns and mental health interventions be used to target frequent social media users and academically struggling adolescents to prevent adverse health outcomes.